Where our protection lies : separation of powers and constitutional review - Kyritsis, Dimitrios, 1978- (Oxford : Oxford University Press, 2017)
Should courts be able to scrutinise primary legislation for its compatibility with human rights? Focusing on the value of the separation of powers, Dimitrios Kyritsis offers an innovative discussion of the role of constitutional courts and the scope of judicial review, and a normative theory of the constitutional review of legislative action.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 21, 2017).
Keywords: Human rights; Separation of powers; Politics and Government; Politics & government